Organization and Work Relationship Patterns of Fishers used Boat Lift Nets in Ballang Lompo Island, South Sulawesi - Andi Adri Arief (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2022)
This study aims to analyze the organization and working relationship of boat lift net fishers, the recruitment system for group members, the form and nature of the employment relationship, and the wage system in fisherman working groups. The research method is qualitative, and the research type is descriptive. Purposefully, the research location was chosen by the defined research challenge. In-depth interviews and observation participation will be used to acquire qualitative data. In this study, data processing and analysis were carried out simultaneously in a process that was carried out continuously since data collection was carried out, especially in organizing, selecting, and categorizing data in the form of narrative descriptions or thick descriptions. The study results indicate that the organization and working relationship of fishers who use lift-net fishing gear on Balang Lompo Island still use local rules that live in the community. These rules regulate cooperative relationships between Ponggawa (owner of production equipment), Ponggawa sea (leader of production activities), and Sawi (workers/subordinates). For the Sawi greens recruitment system, kinship and neighborhood factors are still the main factors compared to other factors. The profit-sharing system applied is one of the local rules inherent in the fishery process. Ritual practices associated with belief in the fishing community on this island are codes of conduct that become rules that are still maintained while making adjustments along with the times.